2013
DOI: 10.1108/md-03-2013-0102
|View full text |Cite
|
Sign up to set email alerts
|

Financial crisis impact on sustainability reporting

Abstract: Purpose – The purpose of this paper is to shed some light on the effect of the current financial crisis on corporate social responsibility (CSR) reporting and CSR assurance strategies that companies disclose online to stakeholders, by dividing the time horizon into two periods, before 2008 and from 2008. Design/methodology/approach – The sample includes Spanish listed companies, differentiating CSR reporters from non CSR-reporters. Also distinguished in the CSR-reporters sample, are those companies that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
4
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 29 publications
4
62
4
8
Order By: Relevance
“…Bansal et al (in press) evidenced empirically that firms reduced their CSR during the 2008-2009 global recession but they showed that firms with greater slack resources are more likely to continue their strategic CSR during times of economic constraint. Similarly, García-Benau et al (2013) evidenced that the number of CSR reports increased significantly with the crisis in Spain. Conversely, others studies argue that environmental and CSR initiatives tend to fall at times of crisis.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 94%
“…Bansal et al (in press) evidenced empirically that firms reduced their CSR during the 2008-2009 global recession but they showed that firms with greater slack resources are more likely to continue their strategic CSR during times of economic constraint. Similarly, García-Benau et al (2013) evidenced that the number of CSR reports increased significantly with the crisis in Spain. Conversely, others studies argue that environmental and CSR initiatives tend to fall at times of crisis.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 94%
“…Some scholars study on the effect of financial crisis and conclude that CSR reporting and assurance may help companies differentiate their products or services from the competition and reinforce the trust from stakeholders, as results show that the number of CSR reports increases significantly with the crisis [17]. Some focus on the motivation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tucker and Pitt [79] observe that performance measurement helps to evaluate and change performance goals and increase value creation. On the other hand, Corporate Social Responsibility could be understood as an evolving concept [15], by which organizations integrate social, environmental and economic concerns into their strategy and decision-making process [28]. According to this view, organizations are disclosing sustainability reports that extend the traditional financial information provided to shareholders with the intention of fulfilling the needs of a wider range of stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…According to this view, organizations are disclosing sustainability reports that extend the traditional financial information provided to shareholders with the intention of fulfilling the needs of a wider range of stakeholders. As a consequence, organizations are redefining their objectives in response to social expectations [28].…”
Section: Resultsmentioning
confidence: 99%